Participation and empowerment in Primary Health Care: from Alma Ata to the era of globalization - Pol De Vos; Geraldine Malaise; Wim De Ceukelaire; Denis Pérez; Pierre Lefèvre; Patrick Van der Stuyft (Social Medicine Publication Group, 2009)
With the 1978 Alma Ata declaration, community participation was brought to the fore as a key component of primary health care. This paper describes how the concepts of people's participation and empowerment evolved throughout the last three decades and how these evolutions are linked with the global changing socio-economic context. On the basis of a literature review and building on empirical experience with grass roots health programs, three key issues are identified to revive these concepts: The recognition that power, power relations and conflicts are the cornerstone of the empowerment framework; the need to go beyond the community and factor in the broader context of the society including the role of the State; and, considering that communities and society are not homogeneous entities, the importance of class analysis in any empowerment framework.